Strengthening of reinforced concrete beam using different configuration on carbon fibre reinforced polymer strips - Sharifah Syazwana, Sayed Hashim (2014)
This paper present the experimental research on- strengthening of reinforced concrete (RC) beams using different configuration of carbon fibre reinforced polymer (CFRP) strips. In general, FRP material is fairly expensive compared to other materials. In order to increase the capacity of structural members damaged by deterioration and overloads or even aggressive environment condition, more economic and effective for building structures have been needed. According to Dong, Wang, & Guan, (2011), it can be seen that the beams retrofitted with CFRP have a much smaller crack width and exhibit a less number of cracks than the control beam. Therefore, difference configurations of CFRP strips have been investigate to provide potentially economical solution. The work carried out is to investigate the effect of different configurations of CFRP strips towards ultimate shear capacity, beam deflection and on crack propagation of the retrofitted beams. The test consists of three reinforced concrete beams which two beam is retrofitted with CFRP strips at preloaded stage and one is not preloaded or retrofitted with CFRP strips and act as a control beam which subjected to four points loading system. Under loaded condition, beams are retrofitted with different configurations of CFRP strips then the load increases until the beams reach failure. Research output has shown that the strengthening effects of CFRP towards shear capacity, beam deflection and on crack propagation of RC beams depend on the arrangements of CFRP. Based on experimental it shows that by using CFRP retrofitted beam in L shape and U shape configuration was proved to be effective because it can reduce the number of crack as well as increased the shear capacity. The experimental result shows that by using CFRP strips in L shape configuration is the most effective configuration in order to improving the ultimate shear capacity and stiffness of a strengthened RC beam. Other than that, from the result it also proved that retrofitted beam in CFRP L shape configuration show the lowest midspan deflection at peak load and least number of cracking after failure compared to others.